Which body mass index is best associated with risk of diabetes mellitus and hypertension in a Japanese-Brazilian population? - Rosana Farah Simony; Suely Godoy Agostinho Gimeno; Sandra Roberta Gouveia Ferreira; Laércio Joel Franco
The objective of this study was to evaluate the impact of different body mass index (BMI) ranges associated with the risk of diabetes and hypertension in Japanese-Brazilians. This cross-sectional study was based on data from 1,330 Japanese-Brazilians > 30 years of age who participated in a population-based survey on the prevalence of diabetes mellitus and associated diseases. Glucose tolerance status was classified according to WHO criteria and blood pressure levels according to the VI-JNC. Odds ratios for diabetes and hypertension were calculated for different BMI ranges; for different BMIs, sensitivity and specificity for percentiles 25, 50, 75, 90 and 95 were obtained. Increased odds ratios for diabetes mellitus and hypertension were observed with BMI values > 25kg/m². The 50th percentile corresponded to the highest sensitivity and specificity for the identification of risk for both diseases. Our results suggest that BMI values proposed by WHO should also be useful for this group of Japanese descendants in the assessment of risk for DM and hypertension.